Effectivity assay of several PGPR strains for controlling collar rot disease (Athelia rolfsii (Curzi)) on soybean (Glycine max (L.) Merril). - Widya Antastia; Irda Safni; Ameilia Zuliyanti Siregar (Jurnal Agroekoteknologi, 2019)
A. rolfsii (Curzi) is a cosmopolitan fungus which infects a large varieties of plants, especially the young one. This study was aimed to test the effectivity of 5 types of plant growth promoting rhizobacteria (PGPR) in suppressing the growth of Athelia rolfsii (Curzi) and to obtain the most effective type of PGPR for controlling disease severity and incidence A. rolfsii. This research was conducted at Plant Disease Laboratory and at the screen house at Faculty of Agriculture, Universitas Sumatera Utara, Medan from March 2017 until August 2017. The research used by non Factorial Randomized Block Design with 7 treatment combinations and 4 replications: R0 (Control), R1 (A. rolfsii), R2 (A. rolfsii+Aeromonas hydrophila), R3 (A. rolfsii+Burkholderia cepacia), R4 (A. rolfsii+Serratia ficaria), R5 (A. rolfsii+Pantoea spp. 2), R6 (A. rolfsii+Vibrio alginolyticus). The results showed that the application of B. cepacia, Pantoea spp. 2, and V. Alginolyticus could suppress the growth of A. rolfsii, with disease incidence was 0.00 % for treatments of B. cepacia, Pantoea spp. 2, and V. alginolyticus compared to the treatment (only A. rolfsii), which was 100.00 %. The disease severity of treatments of B. cepacia, Pantoea spp. 2, and V. alginolyticus was 0.00 % compared to the treatment (only A. rolfsii), which was 50.00 %.